Let [tex]\alpha[/tex] be positive real number.
Let f:[tex]\mathbb{R}\to\mathbb{R}[/tex] and g:[tex](\alpha,\infty)\to\mathbb {R}[/tex] be the function defined by
[tex] \rm f(x) = \sin \bigg( \dfrac{\pi x}{12} \bigg ) \: and \: g(x) = \dfrac{2 log_{e}( \sqrt{x} - \sqrt{ \alpha } ) }{ log_{e}( {e}^{ \sqrt{x} } - {e}^{ \sqrt{ \alpha } } ) } [/tex]
Then the value of [tex] \rm \lim_{x \to { \alpha }^ + } f(g(x)) \\ [/tex] is​

Respuesta :

First, [tex]f(x)[/tex] is continuous on its domain, so

[tex]\displaystyle \lim_{x\to\alpha^+} f(g(x)) = f\left(\lim_{x\to\alpha^+} g(x)\right) \\\\ ~~~~~~~~~~~~~~~~~~ = \sin\left(\frac\pi6 \lim_{x\to\alpha^+} \frac{\ln\left(\sqrt x - \sqrt\alpha\right)}{\ln\left(e^{\sqrt x} - e^{\sqrt\alpha}\right)}\right)[/tex]

As [tex]x\to\alpha^+[/tex], [tex]\sqrt x-\sqrt\alpha\to0[/tex] and [tex]e^{\sqrt x}-e^{\sqrt\alpha}\to0[/tex], so overall we have an indeterminate form ∞/∞. Apply l'Hôpital's rule and simplify.

[tex]\displaystyle \lim_{x\to\alpha^+} f(g(x)) = \sin\left(\frac\pi6 \lim_{x\to\alpha^+} \frac{\frac1{2\sqrt x\left(\sqrt x - \sqrt\alpha\right)}}{\frac{e^{\sqrt x}}{2\sqrt x\left(e^{\sqrt x} - e^{\sqrt\alpha}\right)}}\right) \\\\ ~~~~~~~~~~~~~~~~~~ = \sin\left(-\frac\pi6 \lim_{x\to\alpha^+} \frac{e^{-(\sqrt x-\sqrt\alpha)} - 1}{\sqrt x - \sqrt\alpha}\right)[/tex]

Substitute [tex]y=\sqrt x-\sqrt\alpha[/tex], so that [tex]x\to\alpha^+\implies y\to0^+[/tex].

[tex]\displaystyle \lim_{x\to\alpha^+} f(g(x)) = \sin\left(-\frac\pi6 \lim_{y\to0^+} \frac{e^{-y} - 1}y\right)[/tex]

The remaining limit is the right-derivative of [tex]e^{-y}[/tex] at [tex]y=0[/tex], so

[tex]\displaystyle \lim_{x\to\alpha^+} f(g(x)) = \sin\left(-\frac\pi6\frac{de^{-y}}{dy}\bigg|_{y\to0^+}\right) \\\\ ~~~~~~~~~~~~~~~~~~ = \sin\left(\frac\pi6\right) = \boxed{\frac12}[/tex]

ACCESS MORE